2009
DOI: 10.1212/wnl.0b013e3181a7114b
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric and intrahemispheric language reorganization in complex partial epilepsy

Abstract: Objective: To investigate interhemispheric and intrahemispheric reorganization in patients with localization-related epilepsy. Method:We studied 50 patients with a left hemispheric focus and 20 normal right-handed controls with a 3T echoplanar imaging blood oxygen level dependent functional MRI auditory-based word definition decision task. Data were analyzed using SPM 2. Using region of interest for Broca and Wernicke areas and an asymmetry index (AI), patients were categorized as left language (LL; AI Ն0.20) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 38 publications
5
69
0
Order By: Relevance
“…10 It has been well-documented that increased language task difficulty or linguistic complexity is generally associated with increased magnitude and spatial extent of right hemispheric language cortical activation. [10][11][12] Rosenberger et al, 13 in their study of 50 patients with a left hemispheric seizure focus and 20 right-handed controls, found increased frequency of activation in right hemispheric homologues of Broca area and broadly defined Wernicke area in the patient group, but they did not find evidence for intrahemispheric reorganization in patients who were left-language-dominant.…”
Section: Epilepsy-related Language Plasticitymentioning
confidence: 94%
“…10 It has been well-documented that increased language task difficulty or linguistic complexity is generally associated with increased magnitude and spatial extent of right hemispheric language cortical activation. [10][11][12] Rosenberger et al, 13 in their study of 50 patients with a left hemispheric seizure focus and 20 right-handed controls, found increased frequency of activation in right hemispheric homologues of Broca area and broadly defined Wernicke area in the patient group, but they did not find evidence for intrahemispheric reorganization in patients who were left-language-dominant.…”
Section: Epilepsy-related Language Plasticitymentioning
confidence: 94%
“…The typical left-hemisphere (LH) language lateralization (see Figure 2) may be modulated in neurological condition (Rasmussen and Milner, 1977;Springer et al, 1999), and language representation may be atypical in patients with disorders such as epilepsy (Billingsley et al, 2001;Adcock et al, 2003;Sabbah et al, 2003;Berl et al, 2005Berl et al, , 2014Brázdil et al, 2005;Goldmann and Golby, 2005;Thiel et al, 2006;Lee et al, 2008;Rosenberger et al, 2009;Yu et al, 2011;Dijkstra and Ferrier, 2013).…”
Section: Patterns Of Language Reorganizationmentioning
confidence: 99%
“…Data from epilepsy patients undergoing invasive electrical stimulation mapping (Ojemann et al, 1989) and noninvasive fMRI (Mbwana et al, 2009;Perrone-Bertolotti et al, 2012a) have provided little evidence of this pattern of functional reorganization. Rosenberger et al (2009) showed that patients with LH EZ could recruit LH areas outside the classical 'eloquent regions' to ensure efficient language processing (Mbwana et al, 2009;Perrone-Bertolotti et al, 2012a). Nevertheless, the intrahemispheric pattern of reorganization is more difficult to explore with classical fMRI analysis methods.…”
Section: Patterns Of Language Reorganizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8] fMRI language lateralization also has the potential to allow for the study of brain plasticity in different pathologic states, such as epilepsy and stroke. [9][10][11][12][13][14][15] The mechanisms underlying neuronal plasticity induced by brain lesions are largely unknown. Changes in transcallosal and collateral inhibition of relevant brain areas for language processing have been suggested as underlying mechanisms.…”
mentioning
confidence: 99%